Saying to be a teacher / teacher in writing: authorship and dialogism in the internship reports - Guedes-Pinto, Ana Lúcia (Linha D'Água, 2020)
Choosing the Bakhtinian perspective of enunciative production as a reference, this article aims at problematizing the speaking’s of trainee – students, from a Pedagogy course at a public university in the state of São Paulo, regarding their experiences in elementary school with students and teachers. It is about participatory approach research, with an interpretive analytical aspect, in which the generation of data was developed in the context of the disciplines, on the theoretical-practical aspect of the course forma-tion, in the years 2017 and 2019. Understanding that the internship report genre it is configured as a secondary genre, placed in the academic sphere in which scientific discourse is usually valued and legitimized, we tried to problematize the many ways of saying the students in their written statements. In their discursive production, by taking the authorship of their experience reports in the schools where they intern, their different valuing intonations indicate the different voices as the dialogue, at the same time that make their search for author insertion visible. In the process of appropriating the word of the other, the utterances vividly express the many voices with whom they dialogue in the initial teacher development.